1983
DOI: 10.1111/j.1467-8624.1983.tb00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Confusion between Memories for Thoughts and Memories for Speech

Abstract: The present experiments compared people's abilities to make decisions about the origin of their memories. Experiment 1 demonstrated that 6-year-olds were as good as 17-year-olds in discriminating memories originating from what they said earlier (self-generations) from memories of what another person said earlier (external presentations). However, in both experiments 1 and 2, 6-year-olds were not as good at discriminating what they had said earlier from what they had only thought. The possibility that younger c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
151
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(160 citation statements)
references
References 11 publications
9
151
0
Order By: Relevance
“…In contrast, based on a procedure introduced by Foley, Johnson, and Raye (1983), Farrant et al (1998) found that, against their predictions, high functioning individuals with autism were unimpaired on a reality-monitoring task. In this procedure a list of words was presented sequentially by a voice on an audiotape.…”
Section: Source Monitoring and Autismmentioning
confidence: 86%
See 3 more Smart Citations
“…In contrast, based on a procedure introduced by Foley, Johnson, and Raye (1983), Farrant et al (1998) found that, against their predictions, high functioning individuals with autism were unimpaired on a reality-monitoring task. In this procedure a list of words was presented sequentially by a voice on an audiotape.…”
Section: Source Monitoring and Autismmentioning
confidence: 86%
“…The pattern of results usually obtained for typically developing children is that reality monitoring is the first ability to emerge, with children performing close to adult levels by approximately 6 years of age (e.g., Foley & Johnson, 1985;Parker, 1995). Both external and internal monitoring are later to emerge (e.g., Day, Howie, & Markham, 1998, Foley & Johnson, 1985Foley et al, 1983;Lindsay, Johnson, & Kwon, 1991;Markham, 1991;Parker, 1995). That is, typically developing children find it easiest to report whether the self or other carried out an action and harder to report either which of two other agents had carried out an action or to report when only a single agent, themselves, carried out the action overtly (e.g., said a word outloud) or ''internally' (thought the word silently).…”
Section: Source Monitoring and Autismmentioning
confidence: 99%
See 2 more Smart Citations
“…Foley & Johnson, 1985;Foley, Harris, & Hermann, 1994;Parker, 1995). In addition, several researches have examined external source-monitoring ability to discriminate two other-generated actions (Foley, Johnson, & Raye, 1983;Lindsay, Johnson, & Kwon, 1991).…”
mentioning
confidence: 99%